UTILIZATION OF THE COMMON SIZE METHOD IN ANALYZING POPULATION DATA MANAGEMENT - Turini Turini; Safitri Akbari; Suwandi Suwandi; Mohammad Umar Fakhrudin; Willy Eka Septian (International Journal of Management, Business, and Social Sciences, 2024)
The purpose of this research was to (1) collect data on the total population in Singkup Village, (2) recapitulate population data based on, (a) Gender, (b) Education, (c) Type of Occupation, (d) marital status, (e ) Age, (3) submit a report on the results of recording Village population data to the Head of Singkup Village, Pasawahan District and hold discussions about the follow-up of the results of this research. The method that the writer uses in this research is descriptive qualitative research. The data collection methods used were observation and interviews. The data were processed using the Microsoft Excel application with the common size method. The results of this study indicate that the population in Singkup Village, Pasawahan District - Kuningan Regency is 1,848 people. The male population is 954 people (52%), and women are 894 people (48%). The types of work for the residents of Singkup Village include: farmers, private employees, Soldiers, Civil Servants, Domestic Servants. Businessman. The limitation of this study is that there are no graphs made from the results of processing population data in Singkup Village. The contribution resulting from this research is to broaden the insights and knowledge of students and lecturers in analyzing population data processing using the common size method. The novelty of this study is that the researchers held discussions with the Village Head about what the Village Head would do in responding to residents who did not have permanent jobs.